Rapid assessment of protection and ecological effectiveness of the Spanish Fishing Reserve Network. (April 2018) - Rodríguez-Rodríguez, David
Abstract: Fishing Reserves (FRs) are primarily designated for the enhancement of local fisheries and, secondarily, for biodiversity conservation. In Spain, FRs are considered marine protected areas (MPAs) and included in the country's MPA network. MPAs' ecological effectiveness is linked to a number of legal, managerial and bio-physical factors. With the amount of MPA area rapidly rising and conservation funds largely stagnant or decreasing, rapid, cost-effective MPA assessment techniques are becoming increasingly useful to verify fulfillment of global conservation targets and ascertain potential conservation effectiveness. Here, a rapid MPA protection assessment framework and one MPA ecological effectiveness framework were applied to the Spanish Network of 10 FRs (FRN): the MaPAF and NEOLI frameworks. The FRN was moderately legally protected, with over 50.5% of its area having three or more overlapping legal designations, but only 3.8% of the FRN's area being no-take. All FRs had management plans and active surveillance. According to MaPAF, Columbretes FR was the most highly legally protected whereas Cabo de Palos was the FR with the greatest managerial effort. Both rank highest in protection. In contrast, Masía Blanca FR and Alborán FR were the least legally protected whereas Alborán FR and Graciosa FR were the least managerially protected FRs of the FRN and rank the lowest in protection, respectively. According to the NEOLI framework, Columbretes would also be the most effective FR whereas Masía Blanca FR would be the least ecologically effective. These results can help to spur and better allocate conservation efforts across the fastly growing Spanish MPA network. Highlights: Protection and ecological effectiveness of 10 Spanish Fishing Reserves was assessed. Two rapid assessment frameworks were applied: MaPAF and NEOLI. 64% of the FR area had more than one legal designation, but only 4% was no-take. All fishing reserves had management plans and active surveillance. Protection and ecological effectiveness of the FR Network were moderately high.